All-solid secondary battery
Patent Information
- Application Number
- JP2020187990
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2019-11-11
- Filing Date
- 2020-11-11
- Publication Date
- 2025-02-19
- Estimated Expiration
- 2040-11-11
AI Technical Summary
【0005】 本発明の一側面により、正極層と固体電解質層とが互いに異なる電解質を含む全固体二次電池によれば、短絡が防止され、サイクル特性が向上された全固体二次電池を提供することが可能である。
Smart Images

Figure 0007632801000002 
Figure 0007632801000003 
Figure 0007632801000004
Abstract
Description
[Technical field]
[0001] The present invention relates to an all-solid-state secondary battery. [Background technology]
[0002] Recently, due to industrial demands, batteries with high energy density and excellent safety have been actively developed. For example, lithium ion batteries have been put to practical use not only in the information-related equipment field and the communication equipment field, but also in the automobile field. In the automobile field, safety is particularly important because it is related to life. Currently available lithium ion batteries use a liquid electrolyte layer between the positive electrode layer and the negative electrode layer, so that if a short circuit occurs, overheating and fire may occur. In contrast, an all-solid-state battery using a solid electrolyte layer instead of a liquid electrolyte layer has been proposed. Since the all-solid-state battery does not use a liquid electrolyte layer, the possibility of fire or explosion occurring even if a short circuit occurs can be greatly reduced. Therefore, such an all-solid-state battery can greatly improve safety compared to a lithium ion battery using a liquid electrolyte layer. Summary of the Invention [Problem to be solved by the invention]
[0003] The present invention provides a new all-solid-state secondary battery in which the positive electrode layer and the solid electrolyte layer contain different electrolytes. [Means for solving the problem]
[0004] According to one embodiment, there is provided an all-solid-state secondary battery including a positive electrode layer, a negative electrode layer, and a solid electrolyte layer disposed between the positive electrode layer and the negative electrode layer, wherein the positive electrode layer includes a positive electrode current collector and a positive electrode active material layer disposed on the positive electrode current collector, the negative electrode layer includes a negative electrode current collector and a first negative electrode active material layer disposed on the negative electrode current collector, the positive electrode active material layer includes a porous oxide-based composite solid electrolyte, and the solid electrolyte layer includes a sulfide-based solid electrolyte. Effect of the Invention
[0005] According to one aspect of the present invention, an all-solid-state secondary battery in which a positive electrode layer and a solid electrolyte layer contain different electrolytes can be provided, which prevents short circuits and has improved cycle characteristics. [Brief description of the drawings]
[0006] [Figure 1] 1 is a cross-sectional view of an all-solid-state secondary battery according to an illustrative embodiment; [Diagram 2] 1 is a cross-sectional view of an all-solid-state secondary battery according to an illustrative embodiment; [Diagram 3] 1 is a schematic diagram of a positive electrode layer of an all-solid-state secondary battery according to an illustrative embodiment; FIG. [Figure 4] 1 is a schematic diagram partially illustrating the inside of an all-solid-state secondary battery according to an illustrative embodiment; DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0007] An all-solid-state secondary battery including a sulfide-based solid electrolyte is manufactured by, for example, preparing a laminate by stacking a positive electrode layer, a negative electrode layer, and a solid electrolyte layer, and pressurizing the prepared laminate. However, since the compositions of the positive electrode layer, the negative electrode layer, and the solid electrolyte layer are different from each other, their physical properties such as elastic modulus are also different from each other. Therefore, the pressure required for molding the positive electrode layer, the negative electrode layer, and the solid electrolyte layer are also different from each other. For example, the positive electrode layer includes a positive electrode active material and a sulfide-based solid electrolyte, and a high pressure is required to reduce the interface resistance between the positive electrode active material and the sulfide-based solid electrolyte. That is, the pressure required for molding the positive electrode active material layer is higher than the pressure required for molding the solid electrolyte layer and the negative electrode layer. Therefore, when applying a pressure suitable for molding the positive electrode active material layer, the applied pressure becomes excessively high compared to the pressure required for molding the negative electrode layer and / or the solid electrolyte layer. Therefore, cracks or the like occur in the negative electrode layer and / or the solid electrolyte layer, and as a result, a short circuit of the all-solid-state secondary battery may occur.
[0008] Alternatively, an all-solid-state secondary battery including a sulfide-based solid electrolyte may be manufactured by, for example, separately manufacturing a positive electrode layer, a negative electrode layer, and a solid electrolyte layer by applying different pressures to each layer, and then simply assembling them. In such a case, the surface of the positive electrode layer molded at the highest pressure may be sintered to the highest degree. Therefore, in a simply assembled all-solid-state secondary battery, the interfacial resistance between the positive electrode layer and the solid electrolyte layer may increase, and the cycle characteristics of the all-solid-state secondary battery may deteriorate.
[0009] The all-solid-state secondary battery according to one aspect has a new composition, which prevents short circuits during charging and discharging and improves cycle characteristics.
[0010] The present inventive concept described below can be modified in various ways and can have various embodiments, but specific embodiments are illustrated in the drawings and described in detail. However, they do not limit the present inventive concept to specific embodiments, and should be understood to include all modifications, equivalents, or alternatives included in the technical scope of the present inventive concept.
[0011] The terms used below are merely used to describe specific embodiments and are not intended to limit the present invention. A singular expression includes a plural expression unless the context clearly indicates otherwise. In the following, terms such as "include" or "have" indicate the presence of a feature, number, step, operation, component, part, ingredient, material, or combination thereof described in the specification, and should be understood not to preclude the presence or addition of one or more other features, numbers, steps, operations, components, parts, ingredients, materials, or combinations thereof. In the following, " / " can be interpreted as "and" or "or" depending on the situation.
[0012] In the drawings, the thickness of the various layers and regions may be exaggerated or reduced for clarity. Like parts are designated by the same reference numerals throughout the specification. Throughout the specification, when a part, such as a layer, film, region, or plate, is referred to as being "on" or "above" another part, this includes not only when it is directly on top of the other part, but also when there is an intermediate part therebetween. Throughout the specification, terms such as first and second may be used to describe various components, but the components are not limited by these terms.
[0013] The terms are used only for the purpose of distinguishing one component from another. In this specification and drawings, components having substantially the same functions and configurations are referred to by the same reference numerals, and redundant explanations are omitted.
[0014] The average particle size of the particles is, for example, the volume-cumulative median diameter (D50) measured using a laser diffraction particle sizer.
[0015] Hereinafter, the all-solid-state secondary battery according to the example embodiment will be described in more detail. [All-solid-state secondary battery] The all-solid-state secondary battery according to an embodiment includes a positive electrode layer, a negative electrode layer, and a solid electrolyte layer disposed between the positive electrode layer and the negative electrode layer, the positive electrode layer includes a positive electrode current collector and a positive electrode active material layer disposed on the positive electrode current collector, the negative electrode layer includes a negative electrode current collector and a first negative electrode active material layer disposed on the negative electrode current collector, and the positive electrode active material layer includes a porous oxide-based composite solid electrolyte. The positive electrode active material layer includes a porous oxide-based composite solid electrolyte, and the solid electrolyte layer includes a sulfide-based solid electrolyte, so that the pressure required for manufacturing the all-solid-state secondary battery is reduced. Therefore, cracks and the like that occur during the manufacturing process of the all-solid-state secondary battery are prevented. As a result, the all-solid-state secondary battery is prevented from being short-circuited, and the cycle characteristics of the all-solid-state secondary battery are improved.
[0016] 1 to 4, the all-solid-state secondary battery 1 includes a positive electrode layer 10, negative electrode layers 20, 20a, 20b, and solid electrolyte layers 30, 30a, 30b disposed between the positive electrode layer 10 and the negative electrode layers 20, 20a, 20b. The positive electrode layer 10 includes a positive electrode current collector 11 and positive electrode active material layers 12, 12a, 12b disposed on the positive electrode current collector 11. The negative electrode layers 20, 20a, 20b include negative electrode current collectors 21, 21a, 21b and first negative electrode active material layers 22, 22a, 22b disposed on the negative electrode current collectors 21, 21a, 21b. The positive electrode active material layers 12, 12a, 12b include a porous oxide-based composite solid electrolyte. The solid electrolyte layers 30, 30a, 30b include a sulfide-based solid electrolyte. 1, 3, and 4 show a structure in which a positive electrode active material layer 12 is disposed on one surface of a positive electrode current collector 11, and FIG. 2 shows a structure in which positive electrode active material layers 12a and 12b are disposed on both surfaces of the positive electrode current collector 11.
[0017] [Positive electrode layer] [Porous electrode layer: porous oxide composite solid electrolyte] 1 to 4, the positive electrode layer 10 includes a positive electrode current collector 11 and positive electrode active material layers 12, 12a, and 12b disposed on the positive electrode current collector 11, and the positive electrode active material layers 12, 12a, and 12b include a porous oxide-based composite solid electrolyte.
[0018] Since the positive electrode active material layers 12, 12a, and 12b contain a porous oxide-based composite solid electrolyte, the pressure required for manufacturing the positive electrode layer 10 is lower than the pressure required for manufacturing the solid electrolyte layers 30, 30a, and 30b containing a sulfide-based solid electrolyte. Therefore, in manufacturing the all-solid-state secondary battery, cracks in the solid electrolyte layers 30, 30a, and 30b containing a sulfide-based solid electrolyte due to high pressure can be prevented.
[0019] The porous oxide-based composite solid electrolyte includes, for example, a porous oxide matrix and an electrolyte disposed in the pores of the porous oxide matrix. The porous oxide-based composite solid electrolyte provides ion conductivity while maintaining a solid state by including an ion-conductive electrolyte disposed in the pores of the insulating porous oxide matrix. The porous oxide matrix forms a kind of framework, and the ion-conductive electrolyte is disposed between the framework. The porous oxide-based composite solid electrolyte is, for example, in the form of a solid powder before being applied to a positive electrode layer.
[0020] The porous oxide matrix may be, for example, one or more selected from SiO2, Al2O3, ZrO2, TiO2, ZnO, SnO2 and CeO2, but is not necessarily limited thereto, and may be any oxide having a porous structure that is used in the art. The porous oxide matrix may also be, for example, particulate. The particulate porous oxide matrix may have an average particle size of, for example, 0.5 to 50 μm μm, 1 to 50 μm, 1 to 40 μm, 1 to 30 μm, 1 to 20 μm, 1 to 10 μm, or 1 to 5 μm.
[0021] The porous oxide matrix, for example, contains ordered mesoporous pores. The porous oxide matrix, for example, contains periodically arranged pores. The average diameter of the pores contained in the porous oxide matrix is, for example, 1 nm to 900 nm, 1 nm to 500 nm, 1 nm to 400 nm, 1 nm to 300 nm, 1 nm to 200 nm, 1 nm to 100 nm, 1 nm to 50 nm, 1 nm to 40 nm, 1 nm to 30 nm, 1 nm to 20 nm, or 1 nm to 10 nm. The average diameter of the pores contained in the porous oxide matrix is, for example, measured by nitrogen adsorption method.
[0022] The electrolyte contained in the porous oxide-based composite solid electrolyte includes a lithium salt and a medium, and the medium may include, for example, one or more selected from an organic solvent and an ionic liquid.
[0023] The lithium salt contained in the electrolyte is, for example, one or more selected from LiN(SO2F)2(LiFSI), LiN(SO2CF3)2(LiTFSI), LiSCN, LiN(CN)2, LiClO4, LiBF4, LiAsF6, LiPF6, LiCF3SO3, LiC(CF3SO2)3, LiN(SO2C2F5)2, LiSbF6, LiPF3(CF2CF3)3, LiPF3(CF3)3, and LiB(C2O4)2.
[0024] Examples of organic solvents contained in the electrolyte include N-methylacetamide, ethylene carbonate, propylene carbonate, dimethyl carbonate, fluoroethylene carbonate, diethyl carbonate, ethyl methyl carbonate, poly(ethylene glycol) dimethyl ether (PEGDME, polyglyme), tetra(ethylene glycol) dimethyl ether (TEGDME, tetraglyme), tri(ethylene glycol) dimethyl ether (triglyme), poly(ethylene glycol) dilaurate (PEGDL), poly(ethylene glycol) monoacrylate (PEGMA), poly(ethylene and at least one selected from the group consisting of 1,2-dimethoxy-2-phenylacetophenone, 1,2-dimethoxyethane (DME), 1,2-diethoxyethane, tetrahydrofuran, gamma butyrolactone, 1,1,2,2-tetrafluoroethyl 2,2,3,3-tetrafluoropropyl ether, succinonitrile, adiponitrile, sulfolene, dimethyl sulfone, ethyl methyl sulfone, and diethyl sulfone.
[0025] The ionic liquid contained in the electrolyte may be, for example, one or more cations selected from ammonium, pyrrolidinium, pyridinium, pyrimidinium, imidazolium, piperidinium, pyrazolium, oxazolium, pyridazinium, phosphonium, sulfonium, triazolium, and mixtures thereof; and BF4 - , PF6 - , AsF6 - , SbF6 - , AlCl4 - , HSO4 - , ClO4 - , CH3SO3 - , CF3CO2 - , Cl - , Br - , I - , BF4 - , SO4 - , CF3SO3 - , (FSO2)2N - , (C2F5SO2)2N - , (C2F5SO2)(CF3SO2)N - and (CF3SO2)2N - The ionic liquid is also selected from compounds containing one or more anions selected from the group consisting of N-methyl-N-propylpyrrolidinium bis(trifluoromethanesulfonyl)imide, N-butyl-N-methylpyrrolidinium bis(3-trifluoromethylsulfonyl)imide, 1-butyl-3-methylimidazolium bis(trifluoromethylsulfonyl)amide, and 1-ethyl-3-methylimidazolium bis(trifluoromethylsulfonyl)amide.
[0026] The content of the lithium salt contained in the electrolyte is 1 mol% to 30 mol%, 3 mol% to 30 mol%, 5 mol% to 30 mol%, 10 mol% to 30 mol%, or 15 mol% to 25 mol% based on the total molar amount of the medium including the electrolyte and the lithium salt. When the electrolyte has a lithium salt content in such a range, the cycle characteristics of the all-solid-state secondary battery 1 can be further improved. If the lithium salt content is too low, the internal resistance of the all-solid-state secondary battery 1 increases and the life characteristics deteriorate. If the lithium salt content is too high, a part of the lithium salt is precipitated in the solid, making it difficult to manufacture the porous oxide-based composite solid electrolyte.
[0027] For example, 100 parts by weight of the porous oxide-based composite solid electrolyte may contain 50 to 70 parts by weight of a porous oxide matrix, 20 to 40 parts by weight of a lithium salt, and 5 to 10 parts by weight of a medium. When the porous oxide-based composite solid electrolyte has such a composition, the cycle characteristics of the all-solid-state secondary battery 1 can be further improved.
[0028] The content of the porous oxide-based composite solid electrolyte is, for example, 1 to 30% by weight, 2 to 28% by weight, 5 to 25% by weight, 7 to 23% by weight, or 10 to 20% by weight of the total weight of the positive electrode active material layers 12, 12a, and 12b. When the porous oxide-based composite solid electrolyte has a content in such a range, the cycle characteristics of the all-solid-state secondary battery 1 can be further improved. If the content of the porous oxide-based composite solid electrolyte is too low, the content of lithium ions is too low, which increases the battery resistance, and if the content of the porous oxide-based composite solid electrolyte is too high, the discharge capacity of the all-solid-state secondary battery 1 can be reduced.
[0029] [Positive electrode layer: inactive material] 1 to 4, the positive electrode layer 10 includes a positive electrode current collector 11, positive electrode active material layers 12, 12a, and 12b disposed on the positive electrode current collector 11, and an inactive member 40 disposed on one side of the positive electrode active material layers 12, 12a, and 12b.
[0030] The inactive member 40 is a member that does not contain a material having electrochemical activity, for example, an electrode active material. The electrode active material is a material that absorbs / desorbs lithium. The inactive member 40 is a member that is made of a material other than the electrode active material and is used in the technical field.
[0031] The inactive member 40 may surround the side surfaces of the positive electrode active material layers 12, 12a, and 12b, be disposed in the periphery of the positive electrode current collector 11, be extended to the end portion of the positive electrode current collector 11, and be in contact with the solid electrolyte layers 30, 30a, and 30b. Since the inactive member 40 surrounds the side surfaces of the positive electrode active material layers 12, 12a, and 12b, is disposed in the periphery of the positive electrode current collector 11, be extended to the end portion of the positive electrode current collector 11, and be in contact with the solid electrolyte layers 30, 30a, and 30b, cracks in the solid electrolyte layers 30, 30a, and 30b that are not in contact with the positive electrode active material layers 12, 12a, and 12b due to a pressure difference during a pressing process can be effectively suppressed.
[0032] The inactive member 40 also extends to the end portions of the solid electrolyte layers 30, 30a, 30b. By extending the inactive member 40 to the end portions of the solid electrolyte layers 30, 30a, 30b, it is possible to suppress cracks occurring at the end portions of the solid electrolyte layers 30, 30a, 30b. The end portions of the solid electrolyte layers 30, 30a, 30b are the outermost portions that contact the side surfaces of the solid electrolyte layers 30, 30a, 30b. That is, the inactive member 40 also extends to the outermost portions that contact the side surfaces of the solid electrolyte layers 30, 30a, 30b.
[0033] The area S1 of the positive electrode active material layers 12, 12a, 12b is smaller than the area S2 of the solid electrolyte layers 30, 30a, 30b in contact with the positive electrode active material layers 12, 12a, 12b, and the inactive member 40 is disposed surrounding the side surfaces of the positive electrode active material layers 12, 12a, 12b, thereby correcting the area error between the positive electrode active material layers 12, 12a, 12b and the solid electrolyte layers 30, 30a, 30b. The area S3 of the inactive member 40 corrects the difference between the area S1 of the positive electrode active material layers 12, 12a, 12b and the area S2 of the solid electrolyte layers 30, 30a, 30b, thereby effectively suppressing cracks in the solid electrolyte layers 30, 30a, 30b caused by the pressure difference during the pressurization process described in the claims. For example, the area S1 of the positive electrode active material layer 12, 12a, 12b is less than 100%, 99% or less, 98% or less, 95% or less, 90% or less, 85% or less, or 80% or less of the area S2 of the solid electrolyte layer 30, 30a, 30b. For example, the area S1 of the positive electrode active material layer 12, 12a, 12b is 50% to less than 100%, 50% to 99%, 50% to 98%, 50% to 95%, 60% to 90%, 60% to 85%, or 60% to 80% of the area S2 of the solid electrolyte layer 30, 30a, 30b. If the area S1 of the positive electrode active material layers 12, 12a, 12b is the same as or larger than the area S2 of the solid electrolyte layers 30, 30a, 30b, the positive electrode active material layers 12, 12a, 12b and the negative electrode active material layers 22, 22a, 22b may come into physical contact with each other to cause a short circuit, or the possibility of a short circuit occurring due to overcharging of lithium or the like increases.
[0034] An inactive member 40 is also disposed between the opposing positive electrode current collector 11 and the solid electrolyte layers 30, 30a, 30b, or between the two opposing solid electrolyte layers 30, 30a, 30b. The inactive member 40 can act as a filler that fills the space between the opposing positive electrode current collector 11 and the solid electrolyte layers 30, 30a, 30b, or between the two opposing solid electrolyte layers 30, 30a, 30b.
[0035] The area S1 of the positive electrode active material layer 12, 12a, 12b is smaller than the area S4 of the negative electrode current collector 21, 21a, 21b. For example, the area S1 of the positive electrode active material layer 12, 12a, 12b is less than 100%, 99% or less, 98% or less, 95% or less, 90% or less, 85% or less, or 80% or less of the area S4 of the negative electrode current collector 21, 21a, 21b. For example, the area S1 of the positive electrode active material layer 12, 12a, 12b is 50% to less than 100%, 50% to 99%, 50% to 98%, 50% to 95%, 60% to 90%, 60% to 85%, or 60% to 80% of the area S4 of the negative electrode current collector 21, 21a, 21b.
[0036] The area S4 of the negative electrode current collectors 21, 21a, 21b is the same as the area S5 of the positive electrode current collector 11 and / or the shape thereof. For example, the area S4 of the negative electrode current collectors 21, 21a, 21b is within a range of 100±5%, 100±3%, 100±2%, 100±1%, or 100±0.5% of the area S5 of the positive electrode current collector 11. The area S5 of the positive electrode current collector 11 is the same as the area S2 of the solid electrolyte layers 30, 30a, 30b and / or the shape thereof. For example, the area S5 of the positive electrode current collector 11 is within a range of 100±5%, 100±3%, 100±2%, 100±1%, or 100±0.5% of the area S2 of the solid electrolyte layers 30, 30a, 30b. In this specification, the term "same" area and / or shape includes all cases having "substantially the same" area and / or shape, except where the area and / or shape is intentionally made different.
[0037] The inactive material 40 may include one or more selected from a lithium ion insulator and a lithium ion conductor. The inactive material 40 is also an electronic insulator. That is, the inactive material 40 is not an electronic conductor.
[0038] The inactive member 40 may be an organic material, an inorganic material, or an organic-inorganic composite material. The organic material may be, for example, a polymer. The inorganic material may be, for example, a ceramic such as a metal oxide. The organic-inorganic composite material may be a composite of a polymer and a metal oxide. The inactive member 40 may include, for example, one or more selected from an insulating polymer, an ion-conducting polymer, an insulating inorganic material, an oxide-based solid electrolyte, and a sulfide-based solid electrolyte. The inactive member 40 may be, for example, an olefin-based polymer such as polypropylene (PP) or polyethylene (PE).
[0039] The density of the inactive member 40 may be, for example, 10% to 200%, 10% to 150%, 10% to 140%, 10% to 130%, or 10% to 120% of the density of the positive electrode active material contained in the positive electrode active material layers 12, 12a, and 12b. The density of the inactive member 40 may be, for example, 90 to 110% of the density of the positive electrode active material contained in the positive electrode active material layers 12, 12a, and 12b. The density of the inactive member 40 may be, for example, substantially the same as the density of the positive electrode active material contained in the positive electrode active material layers 12, 12a, and 12b.
[0040] The inactive member 40 may be, for example, a gasket. By using a gasket as the inactive member 40, cracks in the solid electrolyte layers 30, 30a, and 30b caused by the pressure difference during the pressurization process can be effectively suppressed.
[0041] [Cathode layer: Cathode active material] 1 to 4, the positive electrode active material layers 12, 12a, and 12b contain a positive electrode active material.
[0042] The positive electrode active material is a compound that can reversibly absorb and release lithium ions. The positive electrode active material may be, for example, lithium transition metal oxides such as lithium cobalt oxide (LCO), lithium nickel oxide, lithium nickel cobalt oxide, lithium nickel cobalt aluminum oxide (NCA), lithium nickel cobalt manganese oxide (NCM), lithium manganese oxide, and lithium iron phosphate oxide; nickel sulfide; copper sulfide; lithium sulfide; iron oxide or vanadium oxide, but is not necessarily limited thereto, and may be any material that is used as a positive electrode active material in the technical field. The positive electrode active material may be either a single material or a mixture of two or more materials.
[0043] Lithium transition metal oxides include, for example, Li a A 1-b B' b D2 (wherein, in the formula, 0.90≦a≦1 and 0≦b≦0.5); Li a E 1-b B' b O 2-c D c (wherein, 0.90≦a≦1, 0≦b≦0.5, and 0≦c≦0.05); LiE 2-b B' b O 4-c D c (wherein, 0≦b≦0.5 and 0≦c≦0.05); Li a Ni 1-b-c Co b B' c D α (wherein, in the formula, 0.90≦a≦1, 0≦b≦0.5, 0≦c≦0.05, and 0<α≦2); Li a Ni 1-b-c Co b B' c O 2-α F' α (wherein, in the formula, 0.90≦a≦1, 0≦b≦0.5, 0≦c≦0.05, and 0<α<2); Li a Ni 1-b-c Co b B' c O 2-αF'2 (wherein, in the above formula, 0.90≦a≦1, 0≦b≦0.5, 0≦c≦0.05, and 0<α<2); Li a Ni 1-b-c Mn b B' c D α (wherein, in the formula, 0.90≦a≦1, 0≦b≦0.5, 0≦c≦0.05, and 0<α≦2); Li a Ni 1-b-c Mn b B' c O 2-α F' α (wherein, in the formula, 0.90≦a≦1, 0≦b≦0.5, 0≦c≦0.05, and 0<α<2); Li a Ni 1-b-c Mn b B' c O 2-α F'2 (wherein, in the above formula, 0.90≦a≦1, 0≦b≦0.5, 0≦c≦0.05, and 0<α<2); Li a Ni b E c G d O2 (wherein the formula is 0.90≦a≦1, 0≦b≦0.9, 0≦c≦0.5, and 0.001≦d≦0.1); Li a Ni b Co c Mn d GeO2 (wherein the formula is 0.90≦a≦1, 0≦b≦0.9, 0≦c≦0.5, 0≦d≦0.5, and 0.001≦e≦0.1); Li a NiG b O2 (wherein, in the above formula, 0.90≦a≦1, 0.001≦b≦0.1); Li a CoG b O2 (wherein, in the above formula, 0.90≦a≦1, 0.001≦b≦0.1); Li a MnG b O2 (wherein, in the above formula, 0.90≦a≦1, 0.001≦b≦0.1); Li a Mn2G b O4 (wherein the above formula is 0.90≦a≦1, 0.001≦b≦0.1); QO2; QS2; LiQS2; V2O5; LiV2O5; LiI'O2; LiNiVO4; Li (3-f) J2(PO4)3(0≦f≦2);Li (3-f)A compound represented by any one of the chemical formulas Fe2(PO4)3(0≦f≦2);LiFePO4. In such a compound, A is Ni, Co, Mn, or a combination thereof, B' is Al, Ni, Co, Mn, Cr, Fe, Mg, Sr, V, a rare earth element, or a combination thereof, D is O, F, S, P, or a combination thereof, E is Co, Mn, or a combination thereof, F' is F, S, P, or a combination thereof, G is Al, Cr, Mn, Fe, Mg, La, Ce, Sr, V, or a combination thereof, Q is Ti, Mo, Mn, or a combination thereof, I' is Cr, V, Fe, Sc, Y, or a combination thereof, and J is V, Cr, Mn, Co, Ni, Cu, or a combination thereof. A compound having a coating layer added to the surface of such a compound can also be used, and a mixture of the above-mentioned compound and a compound having a coating layer added can also be used. The coating layer added to the surface of such a compound includes, for example, a coating element compound such as an oxide-hydroxide of a coating element, an oxyhydroxide of a coating element, an oxycarbonate of a coating element, or a hydroxycarbonate of a coating element. The compound forming such a coating layer is amorphous or crystalline. The coating element contained in the coating layer is Mg, Al, Co, K, Na, Ca, Si, Ti, V, Sn, Ge, Ga, B, As, Zr, or a mixture thereof. The method of forming the coating layer is selected within a range that does not adversely affect the physical properties of the positive electrode active material. The coating method is, for example, spray coating, immersion, etc. The specific coating method is a content that can be fully understood by those skilled in the art, so a detailed description is omitted.
[0044] The positive electrode active material includes, for example, a lithium salt of a transition metal oxide having a layered rock salt type structure among the aforementioned lithium transition metal oxides. The "layered rock salt type structure" is a structure in which, for example, oxygen atom layers and metal atom layers are regularly arranged alternately in the <111> direction of a cubic rock salt type structure, whereby each atomic layer forms a two-dimensional plane. The "cubic rock salt type structure" indicates a sodium chloride type (NaCl type) structure which is a kind of crystal structure. Specifically, it shows a structure in which face-centered cubic lattices (fcc) formed by cations and anions, respectively, are displaced from each other by about 1 / 2 of the ridge of the unit lattice. Such a lithium transition metal oxide having a layered rock salt type structure is, for example, LiNi x Co y Al z O2 (NCA), LiNi x Co y Mn z O2 (NCM) (0 < x < 1, 0 < y < 1, 0 < z < 1, x + y + z = 1) or LiNi x Co y Mn z Al w O2 (NCMA) (0 < x < 1, 0 < y < 1, 0 < z < 1, 0 < w < 1 and x + y + z + w = 1), which are ternary lithium transition metal oxides. When the positive electrode active material includes a ternary lithium transition metal oxide having a layered rock salt type structure, the energy density and thermal stability of the all-solid-state secondary battery 1 are further improved.
[0045] The positive electrode active material is also covered by a coating layer as described above. The coating layer may be any one as long as it is known as a coating layer for the positive electrode active material of an all-solid-state secondary battery. The coating layer is, for example, Li2O-ZrO2 (LZO) or the like.
[0046] When the positive electrode active material is, for example, LiNi x Co y Al z O2 (NCA) or LiNi x Coy Mn z When the ternary lithium transition metal oxide such as O2(NCM) contains nickel (Ni), it is possible to increase the capacity density of the all-solid-state secondary battery 1 and reduce metal elution from the positive electrode active material in the charged state. As a result, the cycle characteristics of the all-solid-state secondary battery 1 in the charged state are improved.
[0047] The shape of the positive electrode active material is, for example, a particulate shape such as a perfect sphere or an oval sphere. The particle size of the positive electrode active material is not particularly limited, and is within the range applicable to the positive electrode active material of the conventional all-solid-state secondary battery 1. The content of the positive electrode active material in the positive electrode layer 10 is also not particularly limited, and is within the range applicable to the positive electrode layer 10 of the conventional all-solid-state secondary battery 1.
[0048] [Positive electrode layer: binder] The positive electrode active material layers 12, 12a, and 12b may contain a binder, such as styrene butadiene rubber (SBR), polytetrafluoroethylene, polyvinylidene fluoride, or polyethylene.
[0049] [Positive electrode layer: conductive material] The positive electrode active material layers 12, 12a, and 12b may contain a conductive material, such as graphite, carbon black, acetylene black, ketjen black (KB), carbon fiber, or metal powder.
[0050] [Positive electrode layer: Other additives] The positive electrode active material layers 12, 12a, 12b may further contain additives such as a filler, a coating agent, a dispersant, and an ion-conductive auxiliary in addition to the above-mentioned positive electrode active material, solid electrolyte, binder, and conductive material.
[0051] As the filler, coating agent, dispersant, ion-conductive auxiliary agent, and the like contained in the positive electrode active material layers 12, 12a, and 12b, known materials generally used for electrodes of the all-solid-state secondary battery 1 can be used.
[0052] [Positive electrode layer: positive electrode current collector] The positive electrode current collector 11 is, for example, a plate or foil made of indium (In), copper (Cu), magnesium (Mg), stainless steel, titanium (Ti), iron (Fe), cobalt (Co), nickel (Ni), zinc (Zn), aluminum (Al), germanium (Ge), lithium (Li), or an alloy thereof. The positive electrode current collector 11 is optional.
[0053] The positive electrode current collector 11 may further include a carbon layer disposed on one or both sides of the metal substrate. By further disposing a carbon layer on the metal substrate, the metal of the metal substrate is prevented from being corroded by the solid electrolyte contained in the positive electrode layer 10, and the interface resistance between the positive electrode active material layer 12, 12a, 12b and the positive electrode current collector 11 can be reduced. The thickness of the carbon layer is, for example, 1 μm to 5 μm. If the thickness of the carbon layer is too thin, it becomes difficult to completely block the contact between the metal substrate and the solid electrolyte. If the thickness of the carbon layer is too thick, the energy density of the all-solid-state secondary battery 1 decreases. The carbon layer may include amorphous carbon, crystalline carbon, etc.
[0054] [Solid electrolyte layer] [Solid electrolyte layer: solid electrolyte] 1 to 4, the solid electrolyte layers 30, 30a, and 30b are disposed between the positive electrode layer 10 and the negative electrode layers 20, 20a, and 20b, and the solid electrolyte layers 30, 30a, and 30b include a compound-based solid electrolyte.
[0055] Examples of sulfide-based solid electrolytes include Li2S-P2S5, Li2S-P2S5-LiX (X is a halogen element), Li2S-P2S5-Li2O, Li2S-P2S5-Li2O-LiI, Li2S-SiS2, Li2S-SiS2-LiI, Li2S-SiS2-LiBr, Li2S-SiS2-LiCl, Li2S-SiS2-B2S3-LiI, Li2S-SiS2-P2S5-LiI, Li2S-B2S3, and Li2S-P2S5-Z. m S n(m and n are positive numbers, and Z is one of Ge, Zn, and Ga), Li2S-GeS2, Li2S-SiS2-Li3PO4, Li2S-SiS2-Li p MO q (p and q are positive numbers from 0 to 10, and M is one of P, Si, Ge, B, Al, Ga, and In), Li 7-x P.S. 6-x Cl x (0≦x0≦2), Li 7-x P.S. 6-x Br x (0≦x0≦2), and Li 7-x P.S. 6-x I x (0≦x0≦2) is one or more. The sulfide-based solid electrolyte is prepared by processing starting materials such as Li2S and P2S5 by melt quenching or mechanical milling. After such processing, heat treatment can be performed. The solid electrolyte is amorphous, crystalline, or a mixture of them. The solid electrolyte is also, for example, one of the above-mentioned sulfide-based solid electrolyte materials that contains at least sulfur (S), phosphorus (P), and lithium (Li) as constituent elements. For example, the solid electrolyte is also a material that contains Li2S-P2S5. When a sulfide-based solid electrolyte material that contains Li2S-P2S5 is used to form the solid electrolyte, the mixed molar ratio of Li2S and P2S5 is, for example, Li2S:P2S5=50:50 to 90:10.
[0056] Alternatively, the sulfide-based solid electrolyte may include, for example, an Argyrodite-type solid electrolyte represented by the following Chemical Formula 1: (Chemical formula 1) Li + 12-n-x A n+ X 2- 6-x Y' - x
[0057] In the above formula 1, A is P, As, Ge, Ga, Sb, Si, Sn, Al, In, Ti, V, Nb, or Ta, X is S, Se, or Te, and Y' is Cl, Br, I, F, CN, OCN, SCN, or N3, where 1≦n≦5 and 0≦x0≦2. For example, Li 7-x P.S. 6-x Cl x (0≦x≦2), Li 7-x P.S. 6-x Br x (0≦x≦2) and Li 7-x P.S. 6-x I x (0≦x≦2). The sulfide-based solid electrolyte is also an argyrodite-type compound containing one or more selected from Li6PS5Cl, Li6PS5Br, and Li6PS5I.
[0058] The density of the argyrodite-type solid electrolyte is 1.5 to 2.0 g / cc. When the argyrodite-type solid electrolyte has a density of 1.5 g / cc or more, the internal resistance of the all-solid-state secondary battery 1 is reduced, and penetration of the solid electrolyte layers 30, 30a, and 30b by Li can be effectively suppressed.
[0059] The elastic modulus of the sulfide-based solid electrolyte, i.e., Young's modulus, is, for example, 35 GPa or less, 30 GPa or less, 27 GPa or less, 25 GPa or less, or 23 GPa or less. The elastic modulus of the sulfide-based solid electrolyte, i.e., Young's modulus, is, for example, 10 to 35 GPa, 10 to 30 GPa, 10 to 27 GPa, 10 to 25 GPa, or 10 to 23 GPa. Since the sulfide-based solid electrolyte has an elastic modulus in such a range, the temperature and / or pressure required for sintering, etc., is reduced, and the sintering of the solid electrolyte is made easier.
[0060] [Solid electrolyte layer: binder] The solid electrolyte layers 30, 30a, 30b may contain, for example, a binder. The binder contained in the solid electrolyte layers 30, 30a, 30b may be, for example, styrene butadiene rubber (SBR), polytetrafluoroethylene, polyvinylidene fluoride, polyethylene, etc., but is not limited thereto, and any binder used as a binder in the relevant technical field is possible. The binder in the solid electrolyte layers 30, 30a, 30b may be the same as or different from the binder contained in the positive electrode active material layer 12, 12a, 12b and the first negative electrode active material layer 22, 22a, 22b.
[0061] [Negative electrode layer] [Negative electrode layer: negative electrode active material] The negative electrode layers 20, 20a, 20b include first negative electrode active material layers 22, 22a, 22b disposed on the negative electrode current collectors 21, 21a, 21b and on the negative electrode current collectors 21, 21a, 21b. The first negative electrode active material layers 22, 22a, 22b include, for example, a negative electrode active material and a binder.
[0062] The negative electrode active material contained in the first negative electrode active material layer 22, 22a, 22b has, for example, a particulate form. The average particle diameter of the negative electrode active material having a particulate form is, for example, 4 μm or less, 3 μm or less, 2 μm or less, 1 μm or less, or 900 nm or less. The average particle diameter of the negative electrode active material having a particulate form is, for example, 10 nm to 4 μm or less, 10 nm to 3 μm or less, 10 nm to 2 μm or less, 10 nm to 1 μm or less, or 10 nm to 900 nm or less. When the negative electrode active material has an average particle diameter in such a range, reversible absorbing and / or desorbing of lithium during charging and discharging is further facilitated. The average particle diameter of the negative electrode active material is, for example, a median diameter (D50) measured using a laser type particle size distribution meter.
[0063] The negative electrode active material contained in the first negative electrode active material layers 22, 22a, 22b includes, for example, one or more selected from a carbon-based negative electrode active material, a metal negative electrode active material, and a semi-metallic negative electrode active material.
[0064] The carbon-based negative electrode active material is, in particular, amorphous carbon. The amorphous carbon may be, for example, carbon black (CB), acetylene black, furnace black (FB), ketjen black (KB), graphene, etc., but is not necessarily limited thereto, and may be any material that is classified as amorphous carbon in the art. The amorphous carbon is carbon that has no crystallinity or has very low crystallinity, and shows a crystallinity different from that of crystalline carbon or graphite-based carbon.
[0065] The metal negative electrode active material or semi-metal negative electrode active material includes at least one selected from the group consisting of gold (Au), platinum (Pt), palladium (Pd), silicon (Si), silver (Ag), aluminum (Al), bismuth (Bi), tin (Sn) and zinc (Zn), but is not necessarily limited thereto, and may be any metal negative electrode active material or semi-metal negative electrode active material that forms an alloy or compound with lithium in the art. For example, nickel (Ni) does not form an alloy with lithium, and is therefore not a metal negative electrode active material.
[0066] The first negative electrode active material layer 22, 22a, 22b includes one of such negative electrode active materials or a mixture of a plurality of different negative electrode active materials. For example, the first negative electrode active material layer 22, 22a, 22b includes only amorphous carbon or includes one or more selected from the group consisting of gold (Au), platinum (Pt), palladium (Pd), silicon (Si), silver (Ag), aluminum (Al), bismuth (Bi), tin (Sn), and zinc (Zn). Alternatively, the first negative electrode active material layer 22, 22a, 22b includes a mixture of amorphous carbon and one or more selected from the group consisting of gold (Au), platinum (Pt), palladium (Pd), silicon (Si), silver (Ag), aluminum (Al), bismuth (Bi), tin (Sn), and zinc (Zn). The mixing ratio of the amorphous carbon to a mixture of one or more selected from the group consisting of gold (Au), platinum (Pt), palladium (Pd), silicon (Si), silver (Ag), aluminum (Al), bismuth (Bi), tin (Sn) and zinc (Zn) is, for example, 10:1 to 1:2, 5:1 to 1:1, or 4:1 to 2:1, but is not necessarily limited to such ranges, and is selected according to the required characteristics of the all-solid-state secondary battery 1. When the negative electrode active material has such a composition, the cycle characteristics of the all-solid-state secondary battery 1 are further improved.
[0067] The negative electrode active material included in the first negative electrode active material layer 22, 22a, 22b includes a mixture of first particles made of amorphous carbon and second particles made of a metal or a semi-metal. The metal or the semi-metal includes, for example, gold (Au), platinum (Pt), palladium (Pd), silicon (Si), silver (Ag), aluminum (Al), bismuth (Bi), tin (Sn), and zinc (Zn). Alternatively, the semi-metal is a semiconductor. The content of the second particles is 8 to 60 wt%, 10 to 50 wt%, 15 to 40 wt%, or 20 to 30 wt%, based on the total weight of the mixture. When the second particles have a content in such a range, for example, the cycle characteristics of the all-solid-state secondary battery 1 are further improved.
[0068] [Negative electrode layer: binder] The binder contained in the first negative electrode active material layer 22, 22a, 22b may be, for example, styrene butadiene rubber (SBR), polytetrafluoroethylene, polyvinylidene fluoride, polyethylene, vinylidene fluoride / hexafluoropropylene copolymer, polyacrylonitrile, polymethyl methacrylate, etc., but is not necessarily limited thereto, and any binder used in the relevant technical field is possible. The binder may be composed of a single binder or a plurality of different binders.
[0069] The first negative electrode active material layers 22, 22a, 22b contain a binder, so that the first negative electrode active material layers 22, 22a, 22b are stabilized on the negative electrode current collectors 21, 21a, 21b. In addition, cracks in the first negative electrode active material layers 22, 22a, 22b are suppressed despite volume changes and / or relative position changes of the first negative electrode active material layers 22, 22a, 22b during charge and discharge processes. For example, if the first negative electrode active material layers 22, 22a, 22b do not contain a binder, the first negative electrode active material layers 22, 22a, 22b are easily separated from the negative electrode current collectors 21, 21a, 21b. When the first negative electrode active material layer 22, 22a, 22b is detached from the negative electrode collector 21, 21a, 21b, the negative electrode collector 21, 21a, 21b comes into contact with the solid electrolyte layer 30, 30a, 30b at the exposed portion of the negative electrode collector 21, 21a, 21b, increasing the possibility of a short circuit occurring. The first negative electrode active material layer 22, 22a, 22b is produced, for example, by applying a slurry in which the material constituting the first negative electrode active material layer 22, 22a, 22b is dispersed onto the negative electrode collector 21, 21a, 21b and drying the slurry. By including the binder in the first negative electrode active material layer 22, 22a, 22b, the negative electrode active material can be stably dispersed in the slurry. For example, when the slurry is applied onto the negative electrode current collectors 21, 21a, and 21b by a screen printing method, clogging of the screen (for example, clogging due to aggregates of the negative electrode active material) can be suppressed.
[0070] [Negative electrode layer: Other additives] The first negative electrode active material layers 22, 22a, 22b can further contain additives used in conventional all-solid-state secondary batteries 1, such as a filler, a coating agent, a dispersant, an ion-conductive auxiliary, and the like.
[0071] [Negative electrode layer: first negative electrode active material layer] The thickness of the first negative electrode active material layer 22, 22a, 22b is, for example, 50% or less, 40% or less, 30% or less, 20% or less, 10% or less, or 5% or less of the thickness of the positive electrode active material layer 12, 12a, 12b. The thickness of the first negative electrode active material layer 22, 22a, 22b is, for example, 1 μm to 20 μm, 2 μm to 10 μm, or 3 μm to 7 μm. If the thickness of the first negative electrode active material layer 22, 22a, 22b is excessively thin, lithium dendrites formed between the first negative electrode active material layer 22, 22a, 22b and the negative electrode current collector 21, 21a, 21b collapse the first negative electrode active material layer 22, 22a, 22b, and the cycle characteristics of the all-solid-state secondary battery 1 are difficult to improve. If the thickness of the first negative electrode active material layers 22, 22a, 22b becomes excessively large, the energy density of the all-solid-state secondary battery 1 decreases, the internal resistance of the all-solid-state secondary battery 1 due to the first negative electrode active material layers 22, 22a, 22b increases, and it becomes difficult to improve the cycle characteristics of the all-solid-state secondary battery 1.
[0072] If the thickness of the first negative electrode active material layer 22, 22a, 22b is reduced, the charge capacity of the first negative electrode active material layer 22, 22a, 22b is also reduced. The charge capacity of the first negative electrode active material layer 22, 22a, 22b is, for example, 50% or less, 40% or less, 30% or less, 20% or less, 10% or less, 5% or less, or 2% or less of the charge capacity of the positive electrode active material layer 12, 12a, 12b. The charge capacity of the first negative electrode active material layer 22, 22a, 22b is, for example, 0.1% to 50%, 0.1% to 40%, 0.1% to 30%, 0.1% to 20%, 0.1% to 10%, 0.1% to 5%, or 0.1% to 2% of the charge capacity of the positive electrode active material layer 12, 12a, 12b. If the charge capacity of the first negative electrode active material layer 22, 22a, 22b is excessively small, the thickness of the first negative electrode active material layer 22, 22a, 22b becomes very thin, and thus, in a repeated charge / discharge process, lithium dendrites formed between the first negative electrode active material layer 22, 22a, 22b and the negative electrode current collector 21, 21a, 21b collapse the first negative electrode active material layer 22, 22a, 22b, making it difficult to improve the cycle characteristics of the all-solid-state secondary battery 1. If the charge capacity of the first negative electrode active material layer 22, 22a, 22b is excessively large, the energy density of the all-solid-state secondary battery 1 decreases, and the internal resistance of the all-solid-state secondary battery 1 due to the first negative electrode active material layer 22, 22a, 22b increases, making it difficult to improve the cycle characteristics of the all-solid-state secondary battery 1.
[0073] The charge capacity of the positive electrode active material layers 12, 12a, 12b is obtained by multiplying the charge capacity density (mAh / g) of the positive electrode active material by the mass of the positive electrode active material in the positive electrode active material layers 12, 12a, 12b. When multiple types of positive electrode active materials are used, the value of the charge capacity density x mass is calculated for each positive electrode active material, and the sum of these values is the charge capacity of the positive electrode active material layers 12, 12a, 12b. The charge capacity of the first negative electrode active material layers 22, 22a, 22b is also calculated by the same method. That is, the charge capacity of the first negative electrode active material layers 22, 22a, 22b is obtained by multiplying the charge capacity density (mAh / g) of the negative electrode active material by the mass of the negative electrode active material in the first negative electrode active material layers 22, 22a, 22b. When multiple types of negative electrode active materials are used, the value of charge capacity density x mass is calculated for each negative electrode active material, and the sum of these values is the capacity of the first negative electrode active material layer 22, 22a, 22b. Here, the charge capacity density of the positive electrode active material and the negative electrode active material is a capacity estimated using an all-solid-state half-cell using lithium metal as a counter electrode. By measuring the charge capacity using an all-solid-state half-cell, the charge capacity of the positive electrode active material layer 12, 12a, 12b and the first negative electrode active material layer 22, 22a, 22b is directly measured. The charge capacity density is obtained by dividing the measured charge capacity by the mass of each active material. Alternatively, the charge capacity of the positive electrode active material layer 12, 12a, 12b and the first negative electrode active material layer 22, 22a, 22b is also the initial charge capacity measured during the first cycle charge.
[0074] [Negative electrode layer: second negative electrode active material layer] The all-solid-state secondary battery 1 may further include a second negative electrode active material layer disposed between the negative electrode current collector 21, 21a, 21b and the first negative electrode active material layer 22, 22a, 22b by charging. The all-solid-state secondary battery 1 may further include a second negative electrode active material layer disposed between the solid electrolyte layer 30, 30a, 30b and the first negative electrode active material layer 22, 22a, 22b by charging. The second negative electrode active material layer is also a plated layer containing lithium or a lithium alloy. The plated layer is also deposited by charging the battery. The second negative electrode active material layer is a metal layer containing lithium or a lithium alloy. The metal layer contains lithium or a lithium alloy. Therefore, since the second negative electrode active material layer is a metal layer containing lithium, it acts as, for example, a lithium reservoir. The lithium alloy may be, but is not limited to, Li-Al alloy, Li-Sn alloy, Li-In alloy, Li-Ag alloy, Li-Au alloy, Li-Zn alloy, Li-Ge alloy, Li-Si alloy, etc. Any alloy known in the art may be used as a lithium alloy. The second negative electrode active material layer may be made of one of such alloys or lithium, or may be made of multiple alloys.
[0075] The thickness of the second negative electrode active material layer is not particularly limited, and may be, for example, 1 μm to 1,000 μm, 1 μm to 500 μm, 1 μm to 200 μm, 1 μm to 150 μm, 1 μm to 100 μm, or 1 μm to 50 μm. If the thickness of the second negative electrode active material layer is too thin, it is difficult for the second negative electrode active material layer to perform the role of a lithium storage. If the thickness of the second negative electrode active material layer is too thick, the mass and volume of the all-solid-state secondary battery 1 may increase, and the cycle characteristics may be deteriorated.
[0076] In the all-solid-state secondary battery 1, the second negative electrode active material layer is, for example, disposed between the negative electrode current collector 21, 21a, 21b and the first negative electrode active material layer 22, 22a, 22b before assembling the all-solid-state secondary battery 1, or is deposited between the negative electrode current collector 21, 21a, 21b and the first negative electrode active material layer 22, 22a, 22b by charging after assembling the all-solid-state secondary battery 1. When the second negative electrode active material layer is disposed between the negative electrode current collector 21, 21a, 21b and the first negative electrode active material layer 22, 22a, 22b before assembling the all-solid-state secondary battery 1, the second negative electrode active material layer is a metal layer containing lithium, and therefore acts as a lithium storage. For example, a lithium foil is disposed between the negative electrode current collector 21, 21a, 21b and the first negative electrode active material layer 22, 22a, 22b before assembling the all-solid-state secondary battery 1. This further improves the cycle characteristics of the all-solid-state secondary battery 1 including the second negative electrode active material layer. If the second negative electrode active material layer is precipitated by charging after the all-solid-state secondary battery 1 is assembled, the all-solid-state secondary battery 1 does not include the second negative electrode active material layer when assembled, so the energy density of the all-solid-state secondary battery 1 increases. For example, when charging the all-solid-state secondary battery 1, charging is performed beyond the charge capacity of the first negative electrode active material layers 22, 22a, 22b. That is, the first negative electrode active material layers 22, 22a, 22b are overcharged. At the beginning of charging, lithium is absorbed into the first negative electrode active material layers 22, 22a, 22b. The negative electrode active material included in the first negative electrode active material layers 22, 22a, 22b forms an alloy or a compound with the lithium ions that have moved from the positive electrode layer 10. If charging is performed beyond the capacity of the first negative electrode active material layer 22, 22a, 22b, for example, lithium is deposited on the back surface of the first negative electrode active material layer 22, 22a, 22b, i.e., between the negative electrode current collector 21, 21a, 21b and the first negative electrode active material layer 22, 22a, 22b, and a metal layer corresponding to the second negative electrode active material layer is formed by the deposited lithium. The second negative electrode active material layer is a metal layer mainly composed of lithium (i.e., metallic lithium). Such a result is obtained, for example, by the negative electrode active material contained in the first negative electrode active material layer 22, 22a, 22b being composed of a material that forms an alloy or a compound with lithium. During discharge, the lithium in the first negative electrode active material layer 22, 22a, 22b and the second negative electrode active material layer, i.e., the metal layer, is ionized and moves to the positive electrode layer 10 side.Therefore, in the all-solid-state secondary battery 1, lithium can be used as the negative electrode active material. In addition, the first negative electrode active material layer 22, 22a, 22b covers the second negative electrode active material layer, and therefore serves as the second negative electrode active material layer, i.e., a metal layer protective layer, and also serves to suppress the precipitation growth of lithium dendrites. Therefore, the short circuit and capacity reduction of the all-solid-state secondary battery 1 are suppressed, and as a result, the cycle characteristics of the all-solid-state secondary battery 1 are improved. In addition, after the all-solid-state secondary battery 1 is assembled, when the second negative electrode active material layer is disposed by charging, the negative electrode current collectors 21, 21a, 21b and the first negative electrode active material layers 22, 22a, 22b, and the regions therebetween are Li-free regions that do not contain lithium (Li), for example, in the initial state or after discharge state of the all-solid-state secondary battery 1.
[0077] [Negative electrode layer: negative electrode current collector] The negative electrode current collectors 21, 21a, 21b are made of a material that does not react with lithium, i.e., does not form any alloy or compound. The material constituting the negative electrode current collectors 21, 21a, 21b may be, for example, copper (Cu), stainless steel, titanium (Ti), iron (Fe), cobalt (Co) or nickel (Ni), but is not necessarily limited thereto, and any material that is used as an electrode current collector in the relevant technical field is possible. The negative electrode current collectors 21, 21a, 21b are made of one of the above-mentioned metals, or an alloy of two or more metals, or a coating material. The negative electrode current collectors 21, 21a, 21b are, for example, in the form of a plate or foil.
[0078] The all-solid-state secondary battery 1 may further include, for example, a thin film containing an element capable of forming an alloy with lithium on the negative electrode current collector 21, 21a, 21b. The thin film is disposed between the negative electrode current collector 21, 21a, 21b and the first negative electrode active material layer 22, 22a, 22b. The thin film contains, for example, an element capable of forming an alloy with lithium. The element capable of forming an alloy with lithium may be, for example, gold, silver, zinc, tin, indium, silicon, aluminum, bismuth, etc., but is not necessarily limited thereto, and any element capable of forming an alloy with lithium in the relevant technical field is possible. The thin film is composed of one of these metals, or composed of an alloy of multiple metals. By disposing the thin film on the negative electrode current collectors 21, 21a, 21b, for example, the deposition form of the second negative electrode active material layer deposited between the thin film and the first negative electrode active material layers 22, 22a, 22b can be further flattened, and the cycle characteristics of the all-solid-state secondary battery 1 can be further improved.
[0079] The thickness of the thin film is, for example, 1 nm to 800 nm, 10 nm to 700 nm, 50 nm to 600 nm, or 100 nm to 500 nm. If the thickness of the thin film is less than 1 nm, the function of the thin film is difficult to be exerted. If the thickness of the thin film is excessively thick, the thin film itself absorbs lithium, the amount of lithium precipitation in the negative electrode decreases, the energy density of the all-solid-state battery decreases, and the cycle characteristics of the all-solid-state secondary battery 1 deteriorates. The thin film is also disposed on the negative electrode current collectors 21, 21a, and 21b by, for example, a vacuum deposition method, a sputtering method, a plating method, or the like, but is not necessarily limited to such a method, and any method that can form a thin film in the technical field is possible. EXAMPLES
[0080] The present invention will be described in more detail with reference to the following examples and comparative examples, however, the examples are intended to illustrate the present invention and are not intended to limit the scope of the present invention.
[0081] "Example 1: 10 wt% porous solid electrolyte, 85.5 wt% positive electrode active material, SiO2 / LiN(SO2CF3)2(LiTFSI) / methylacetamide (MAc)" (Negative electrode layer manufacturing) A 10 μm thick Ni foil was prepared as a negative electrode current collector, and carbon black (CB) with a primary particle size of about 30 nm and silver (Ag) particles with an average particle size of about 60 nm were prepared as a negative electrode active material.
[0082] 0.25g of mixed powder obtained by mixing carbon black (CB) and silver (Ag) particles at a weight ratio of 3:1 was placed in a container, and 2g of N-methyl-2-pyrrolidone (NMP) solution containing 7% by weight of polyvinylidene fluoride (PVDF) binder (Kureha #9300) was added thereto to prepare a mixed solution. Next, the mixed solution was stirred while adding NMP little by little to the mixed solution to prepare a slurry. The prepared slurry was applied to Ni foil using a bar coater, and dried in a convection oven at 80°C for 10 minutes to obtain a laminate. The obtained laminate was vacuum dried at 40°C for 10 hours. Through the above process, a negative electrode layer in which a first negative electrode active material layer was formed on a negative electrode current collector was manufactured.
[0083] (Manufacturing of solid electrolyte layer) An acrylic binder (SX-A334, Zeon Co., Ltd.) was added to octyl acetate to prepare a 4 wt% binder solution. The prepared acrylic binder solution was added to an argyrodite-type crystal Li6PS5Cl solid electrolyte (D50=3μm, crystalline) and mixed with a Thinky mixer to prepare a slurry. The slurry contained 1.5 parts by weight of an acrylic binder with respect to 98.5 parts by weight of the solid electrolyte. The prepared slurry was applied to a nonwoven fabric using a bar coater and dried for 10 minutes in a convection oven at 80°C to obtain a laminate. The obtained laminate was vacuum-dried at 70°C for 2 hours. A solid electrolyte layer was manufactured by the above process.
[0084] (Manufacturing of negative electrode layer / solid electrolyte layer assembly) A solid electrolyte layer was disposed on the first negative electrode active material layer of the negative electrode layer to prepare a laminate. The prepared laminate was subjected to a hot plate press treatment at 90°C and a pressure of 500 MPa for 10 minutes to prepare a negative electrode layer / solid electrolyte layer assembly. Such a pressurization treatment sinters the solid electrolyte layer, improving the battery characteristics. The thickness of the sintered solid electrolyte layer was about 45 μm. The thickness of the pressed first negative electrode active material layer was about 7 μm.
[0085] (Positive electrode layer manufacturing) (Production of porous oxide composite solid electrolyte) LiTFSI was added to N-methylacetamide to prepare a LiTFSI 20 mol% electrolyte solution. Tetraethyl orthosilicate (TEOS) 50.0 mL was mixed with 26.5 M formic acid aqueous solution 74.0 mL to prepare a silica precursor solution. A gel-state composition was prepared by mixing 133.4 g of LiTFSI 20 mol% electrolyte solution and 255.9 g of silica precursor solution. The gel-state composition was hardened to obtain a precipitate. The obtained precipitate was dried in a convection oven at 50°C for 48 hours and vacuum dried at 80°C for 48 hours to produce a porous oxide composite solid electrolyte powder.
[0086] (Production of positive electrode active material layer) As the positive electrode active material, LiNi 0.8 Co 0.15 Mn 0.05O2 (NCM) was prepared. The porous oxide composite solid electrolyte prepared above was used as the solid electrolyte. Polytetrafluoroethylene (PTFE) binder (DuPont's Teflon (registered trademark) binder) was prepared as the binder. Carbon black (CB) and carbon nanofiber (CNF) were prepared as the conductive material. Such materials were mixed with xylene solvent in a weight ratio of positive electrode active material: porous oxide composite solid electrolyte: carbon black: carbon nanotube: binder = 85.5: 10: 1.5: 1.5: 1.5 to form a positive electrode active material composition into a sheet, and then vacuum dried at 40 ° C for 8 hours to prepare a positive electrode sheet. A gasket made of polypropylene (PP) material was placed around the positive electrode sheet to surround the positive electrode sheet. The positive electrode sheet with the side surrounded by the gasket was pressed onto one side of a positive electrode current collector made of 18 μm thick carbon-coated aluminum foil to prepare a positive electrode layer. The thickness of the positive electrode active material layer and the gasket included in the positive electrode layer was about 100 μm.
[0087] The positive electrode sheet was pressed onto one surface of the positive electrode current collector by roll pressing at a pressure of 450 MPa for 100 ms.
[0088] The positive electrode active material layer was disposed at the center of the positive electrode current collector, and a gasket was disposed to surround the positive electrode active material layer and extend to an end portion of the positive electrode current collector.
[0089] The area of the positive electrode active material layer was about 90% of the area of the positive electrode current collector, and a gasket was placed on the entire surface of the remaining 10% of the positive electrode current collector on which the positive electrode active material layer was not placed.
[0090] (Manufacturing all-solid-state secondary batteries) The prepared positive electrode layer was placed on the solid electrolyte layer of the prepared negative electrode layer / solid electrolyte layer assembly to prepare a laminate. The laminate was placed in a pouch and vacuum sealed to produce an all-solid-state secondary battery. A part of the positive electrode current collector and a part of the negative electrode current collector were protruded outside the sealed battery and used as a positive electrode layer terminal and a negative electrode layer terminal.
[0091] "Example 2: 10 wt% porous solid electrolyte, 85.5 wt% positive electrode active material, SiO2 / LiTFSI / 1,2-dimethoxyethane (DME)" An all-solid-state secondary battery was manufactured in the same manner as in Example 1, except that dimethoxyethane (DME) was used instead of N-methylacetamide (n-MAc) as a medium when preparing the porous oxide composite solid electrolyte.
[0092] "Example 3: Porous solid electrolyte 5wt%, positive electrode active material 90.5wt%, SiO2 / LiTFSI / MAc" An all-solid-state secondary battery was manufactured in the same manner as in Example 1, except that the content of the porous oxide composite solid electrolyte was changed to 5 wt% and the content of the positive electrode active material was changed to 90.5 wt% when manufacturing the positive electrode layer.
[0093] "Example 4: Porous solid electrolyte 15wt%, positive electrode active material 80.5wt%, SiO2 / LiTFSI / MAc" An all-solid-state secondary battery was manufactured in the same manner as in Example 1, except that the content of the porous oxide composite solid electrolyte was changed to 15 wt% and the content of the positive electrode active material was changed to 80.5 wt% when manufacturing the positive electrode layer.
[0094] "Example 5: Porous solid electrolyte 30wt%, positive electrode active material 65.5wt%, SiO2 / LiTFSI / MAc" An all-solid-state secondary battery was manufactured in the same manner as in Example 1, except that the content of the porous oxide composite solid electrolyte was changed to 30 wt% and the content of the positive electrode active material was changed to 65.5 wt% when manufacturing the positive electrode layer.
[0095] "Example 6: Porous solid electrolyte 10wt%, positive electrode active material 85.5wt%, SiO2 / LiN(SO2F)2(LiFSI) / MAc" An all-solid-state secondary battery was manufactured in the same manner as in Example 1, except that LiFSI was used instead of LiTFSI as the lithium salt when preparing the porous oxide composite solid electrolyte.
[0096] "Example 7: Porous solid electrolyte 10wt%, positive electrode active material 85.5wt%, SiO2 / LiTFSI / MAc" When manufacturing the positive electrode layer, LiNi 0.8 Co 0.15 Mn 0.05 LiNi coated with Li2O-ZrO2 (LZO) instead of O2 (NCM) 0.8 Co 0.15 Mn 0.05 An all-solid-state secondary battery was manufactured in the same manner as in Example 1, except that O2(NCM) was used. The LZO-coated positive electrode active material was prepared according to the method disclosed in Korean Patent Publication No. 10-2016-0064942. The thickness of the coated LZO was about 10 nm.
[0097] "Comparative Example 1: Sulfide-based solid electrolyte 15wt%, positive electrode active material 80.5wt%, warm isostactic press" (Negative electrode layer manufacturing) A 10 μm thick Ni foil was prepared as a negative electrode current collector, and carbon black (CB) with a primary particle size of about 30 nm and silver (Ag) particles with an average particle size of about 60 nm were prepared as a negative electrode active material.
[0098] 0.25g of mixed powder obtained by mixing carbon black (CB) and silver (Ag) particles at a weight ratio of 3:1 was placed in a container, and 2g of NMP solution containing 7% by weight of PVDF binder (Kureha #9300) was added thereto to prepare a mixed solution. Next, the mixed solution was stirred while adding NMP little by little to the mixed solution to prepare a slurry. The prepared slurry was applied to Ni foil using a bar coater, and dried for 10 minutes in a convection oven at 80°C to obtain a laminate. The obtained laminate was vacuum dried at 40°C for 10 hours. Through the above process, a negative electrode layer in which a first negative electrode active material layer was formed on a negative electrode current collector was manufactured.
[0099] (Manufacturing of solid electrolyte layer) An acrylic binder (SX-A334, Zeon Co., Ltd.) was added to octyl acetate to prepare a 4 wt% binder solution. The prepared acrylic binder solution was added to an argyrodite-type crystal Li6PS5Cl solid electrolyte (D50=3 μm, crystalline), and mixed with a Thinky mixer to prepare a slurry. The slurry contained 1.5 parts by weight of an acrylic binder with respect to 98.5 parts by weight of the solid electrolyte. The produced slurry was applied to a nonwoven fabric using a bar coater and dried in air at a temperature of 80° C. for 10 minutes to obtain a laminate. The obtained laminate was vacuum-dried at 80° C. for 10 hours. A solid electrolyte layer was produced by the above process.
[0100] (Positive electrode layer manufacturing) As the positive electrode active material, LiNi 0.8 Co 0.15 Mn 0.05 O2 (NCM) was prepared. The porous oxide composite solid electrolyte prepared above was used as the solid electrolyte. Polytetrafluoroethylene (PTFE) binder (DuPont's Teflon (registered trademark) binder) was prepared as the binder. Carbon black (CB) and carbon nanofiber (CNF) were prepared as the conductive material. Such materials were mixed with xylene solvent in a weight ratio of positive electrode active material: sulfide-based solid electrolyte: carbon black: carbon nanotube: binder = 80.5: 15: 1.5: 1.5: 1.5 to form a positive electrode active material composition into a sheet, and then vacuum dried at 40 ° C for 8 hours to prepare a positive electrode sheet. A gasket made of polypropylene (PP) material was placed around the positive electrode sheet to surround the positive electrode sheet. The positive electrode sheet surrounded by the gasket was pressed onto one side of a positive electrode current collector made of 18 μm thick carbon-coated aluminum foil to prepare a positive electrode layer. The thickness of the positive electrode active material layer and the gasket included in the positive electrode layer was about 100 μm.
[0101] The positive electrode active material layer was disposed at the center of the positive electrode current collector, and a gasket was disposed around the positive electrode active material layer, extending to the end of the positive electrode current collector. The positive electrode active material layer had an area of about 90% of the positive electrode current collector area, and the gasket was disposed over the entire surface of the remaining 10% of the positive electrode current collector on which the positive electrode active material layer was not disposed.
[0102] (Manufacturing all-solid-state secondary batteries) A solid electrolyte layer was placed on one side of the positive electrode layer, and a negative electrode layer was placed on the solid electrolyte layer so that the first negative electrode active material layer was in contact with the solid electrolyte layer, to prepare a laminate. The prepared laminate was subjected to a warm isostatic press treatment at 80°C and a pressure of 500 MPa for 30 minutes. Such a pressurization treatment sinters the solid electrolyte layer, improving the battery characteristics. The thickness of the sintered solid electrolyte layer was about 45 μm. The thickness of the pressed first negative electrode active material layer was about 7 μm.
[0103] The pressurized laminate was placed in a pouch and vacuum sealed to produce an all-solid-state secondary battery. A portion of the positive electrode current collector and a portion of the negative electrode current collector were protruded outside the sealed battery to be used as a positive electrode layer terminal and a negative electrode layer terminal.
[0104] "Comparative Example 2: 15 wt% sulfide-based solid electrolyte, 80.5 wt% Li2O-ZrO2 (LZO) coated positive electrode active material, no first negative electrode active material layer, warm isotactic press" The first negative electrode active material layer is not formed, and only the Ni negative electrode current collector is used. When the positive electrode layer 10 is manufactured, LiNi 0.8 Co 0.15 Mn 0.05 LiNi coated with Li2O-ZrO2 (LZO) instead of O2 (NCM) 0.8 Co 0.15 Mn 0.05 An all-solid-state secondary battery was manufactured in the same manner as in Comparative Example 1, except that O2(NCM) was used.
[0105] "Comparative Example 3: No first negative electrode active material layer" An all-solid-state lithium battery was manufactured in the same manner as in Comparative Example 1, except that the first negative electrode active material layer was not formed and only a Ni negative electrode current collector was used.
[0106] "Comparative Example 4: Ni alone" An all-solid-state lithium battery was manufactured in the same manner as in Comparative Example 1, except that nickel (Ni) particles having an average particle size of 100 nm were used instead of a 3:1 weight ratio mixture of carbon black (CB) having a primary particle size of about 30 nm and silver (Ag) particles having an average particle size of about 60 nm as the negative active material.
[0107] "Evaluation example 1: Charge / discharge test" The charge / discharge characteristics of the all-solid-state secondary batteries produced in Examples 1 to 7 and Comparative Examples 1 to 4 were evaluated by the following charge / discharge test. The charge / discharge test was performed by placing the all-solid-state secondary batteries in a thermostatic chamber at 45°C.
[0108] The first cycle was 0.6 mA / cm until the battery voltage reached 3.9 V to 4.25 V. 2 The battery was charged for 12.5 hours at a constant current of 0.6 mA / cm until the battery voltage reached 2.5 V. 2 The battery was discharged for 12.5 hours at a constant current of 1000 V. The discharge capacity of the first cycle was taken as the standard capacity. After the second cycle, charging and discharging were repeated up to 120 cycles under the same conditions as the first cycle. After the second cycle, the number of cycles at which the discharge capacity reached 80% of the standard capacity was determined and the life characteristics were classified in Table 1 according to the following evaluation criteria.
[0109] In addition, whether or not a short circuit occurred during charging and discharging was evaluated, and the results are shown in the following Table 1. If a short circuit occurred, it was marked as "short circuit."
[0110] Evaluation criteria ×: 2nd to 5th cycle △: 6th to 50th cycle 〇: 100th cycle or more
[0111] [Table 1]
[0112] The all-solid-state secondary batteries of Examples 1 to 7 had good life characteristics, with the number of cycles at which the capacity reached 80% of the standard capacity being 6 or more. The all-solid-state secondary batteries of Examples 1, 4 and 7 had excellent life characteristics, with the number of cycles at which they reached 80% of the standard capacity being 100 cycles or more. The all-solid-state secondary battery of Comparative Example 1 had a good life characteristic, with the number of cycles at which the battery reached 80% of the standard capacity being 6 or more. Therefore, the all-solid-state secondary batteries of Examples 1 to 7 exhibited life characteristics equal to or greater than that of the all-solid-state secondary battery of Comparative Example 1.
[0113] The all-solid-state secondary battery of Comparative Example 2 had poor life characteristics, with the number of cycles at which it reached 80% of the standard capacity being 5 cycles or less, and a short circuit occurred before reaching the 5th cycle. In the all-solid-state secondary batteries of Comparative Examples 3 and 4, a short circuit occurred during the charging process of the first cycle or during the discharging process of the first cycle.
[0114] In the all-solid-state secondary batteries of Examples 1 to 7, after the first cycle charging was completed, SEM images of the cross sections of the batteries were measured, and it was confirmed that a deposition layer (i.e., a lithium metal layer) corresponding to the second negative electrode active material layer was formed (i.e., precipitated) between the first negative electrode active material layer and the negative electrode current collector.
[0115] As described above, the all-solid-state secondary battery according to this embodiment is applicable to various portable devices, vehicles, and the like.
[0116] Although an illustrative embodiment has been described in detail with reference to the attached drawings, the present invention is not limited to such an embodiment. It is obvious that a person skilled in the art in the technical field to which the present invention belongs can derive various modifications or alterations within the scope of the technical idea described in the claims, and it goes without saying that these also belong to the technical scope of the present invention. [Explanation of symbols]
[0117] 1 All-solid-state secondary battery 10 Positive electrode layer 11 Positive electrode current collector 12,12a,12b Positive electrode active material layer 20,20a,20b negative electrode layer 21,21a,21b Negative electrode current collector 22,22a,22b First negative electrode active material layer 30,30a,30b solid electrolyte layer 40 Inert Materials
Claims
1. a positive electrode layer, a negative electrode layer, and a solid electrolyte layer disposed between the positive electrode layer and the negative electrode layer; the positive electrode layer includes a positive electrode current collector and a positive electrode active material layer disposed on the positive electrode current collector, the negative electrode layer includes a negative electrode current collector and a first negative electrode active material layer disposed on the negative electrode current collector, the positive electrode active material layer contains a porous oxide-based composite solid electrolyte, the solid electrolyte layer includes a sulfide-based solid electrolyte, an inactive member surrounding one or more side surfaces of the positive electrode active material layer and the positive electrode current collector; the inactive member is disposed on the periphery of the solid electrolyte layer and extends to an end portion of the solid electrolyte layer; The porous oxide-based composite solid electrolyte includes a porous oxide matrix and an electrolyte disposed in pores of the porous oxide matrix, The inactive member does not contain a substance having electrochemical activity and is a member containing a lithium ion insulator.
2. The porous oxide matrix is SiO 2 , Al 2 O 3 , ZrO 2 , TiO 2 , ZnO, SnO 2 and CeO 2 The all-solid-state secondary battery according to claim 1 , comprising one or more selected from the following:
3. The all-solid-state secondary battery according to claim 1 or 2, wherein the porous oxide matrix comprises ordered mesoporous pores.
4. The all-solid-state secondary battery according to claim 1 , wherein the electrolyte comprises a lithium salt and a medium, and the medium comprises one or more selected from the group consisting of an organic solvent and an ionic liquid.
5. The all-solid-state secondary battery according to claim 4, wherein the lithium salt is present in an amount of 1 to 30 mol % based on the total molar amount of the medium and the lithium salt.
6. The lithium salt is LiN(SO 2 F) 2 (LiFSI), LiN(SO 2 CF 3 ) 2 (LiTFSI), LiSCN, LiN(CN) 2 , LiClO 4 , LiBF 4 , LiAsF 6 , LiPF 6 , LiCF 3 SO 3 , LiC(CF 3 SO 2 ) 3 , LiN(SO 2 C 2 F 5 ) 2 , LiSbF 6 , LiPF 3 (CF 2 CF 3 ) 3 , LiPF 3 (CF 3 ) 3 and LiB(C 2 O 4 ) 2 The all-solid-state secondary battery according to claim 4 or 5, comprising one or more selected from the following:
7. The medium contains at least an organic solvent, and the organic solvent is selected from the group consisting of N-methylacetamide, ethylene carbonate, propylene carbonate, dimethyl carbonate, fluoroethylene carbonate, diethyl carbonate, ethyl methyl carbonate, poly(ethylene glycol) dimethyl ether (PEGDME, polyglyme), tetra(ethylene glycol) dimethyl ether (TEGDME, tetraglyme), tri(ethylene glycol) dimethyl ether (triglyme), poly(ethylene glycol) dilaurate (PEGDL), poly(ethylene glycol) monoacrylate (PEGMA), poly(ethylene glycol) diacrylate (PEGD A), 3-dioxolane, 4,5-diethyl-1,3-dioxolane, 4,5-dimethyl-1,3-dioxolane, 4-methyl-1,3-dioxolane, 4-ethyl-1,3-dioxolane, 2,2-dimethoxy-2-phenylacetophenone, 1,2-dimethoxyethane (DME), 1,2-diethoxyethane, tetrahydrofuran, gamma butyrolactone, 1,1,2,2-tetrafluoroethyl 2,2,3,3-tetrafluoropropyl ether, succinonitrile, adiponitrile, sulfolene, dimethyl sulfone, ethyl methyl sulfone and diethyl sulfone. The all-solid-state secondary battery according to any one of claims 4 to 6, comprising one or more selected from the group consisting of.
8. The medium includes at least an ionic liquid, the ionic liquid being one or more cations selected from ammonium, pyrrolidinium, pyridinium, pyrimidinium, imidazolium, piperidinium, pyrazolium, oxazolium, pyridazinium, phosphonium, sulfonium, triazolium, and mixtures thereof; and BF 4 - , P.F. 6 - , AsF 6 - , SbF 6 - , AlCl 4 - , H.S.O. 4 - , ClO 4 - , C.H. 3 SO 3 - , C.F. 3 CO 2 - , Cl - , B - , I - , B.F. 4 - , S.O. 4 - , C.F. 3 SO 3 - , (FSO 2 ) 2 N - , (C 2 F 5 SO 2 ) 2 N - , (C 2 F 5 SO 2 ) (CF 3 SO 2 ) N - and (CF 3 SO 2 ) 2 N - The all-solid-state secondary battery according to claim 4 , wherein the anion is selected from the group consisting of compounds containing one or more anions selected from the group consisting of
9. 9. The all-solid-state secondary battery according to claim 1, comprising 50 to 70 parts by weight of a porous oxide matrix, 20 to 40 parts by weight of a lithium salt, and 5 to 10 parts by weight of a medium, relative to 100 parts by weight of the porous oxide-based composite solid electrolyte.
10. 10. The all-solid-state secondary battery of claim 1, wherein the content of the porous oxide-based composite solid electrolyte is 1 wt % to 30 wt % of the total weight of the positive electrode active material layer.
11. The all-solid-state secondary battery according to claim 1 , further comprising a carbon layer disposed between the positive electrode current collector and the positive electrode active material layer.
12. The sulfide-based solid electrolyte is Li 2 S-P 2 S 5 , Li 2 S-P 2 S 5 -LiX (X is a halogen element), Li 2 S-P 2 S 5 -Li 2 O., Li 2 S-P 2 S 5 -Li 2 O-LiI, Li 2 S-SiS 2 , Li 2 S-SiS 2 - LiI, Li 2 S-SiS 2 - LiBr, Li 2 S-SiS 2 -LiCl, Li 2 S-SiS 2 -B 2 S 3 - LiI, Li 2 S-SiS 2 -P 2 S 5 - LiI, Li 2 S-B 2 S 3 , Li 2 S-P 2 S 5 -Z m S n (m and n are positive numbers, and Z is one of Ge, Zn, and Ga), Li 2 S-GeS 2 , Li 2 S-SiS 2 -Li 3 P.O. 4 , and Li 2 S-SiS 2 -Li p M.O. q (p and q are positive numbers, and M is one of P, Si, Ge, B, Al, Ga, and In). The all-solid-state secondary battery according to any one of claims 1 to 11,
13. The sulfide-based solid electrolyte is Li 7 PS6 and / or Li 2 P 2 The all-solid-state secondary battery according to claim 1 , further comprising:
14. The all-solid-state secondary battery according to any one of claims 1 to 11, wherein the sulfide-based solid electrolyte comprises an argyrodite-type solid electrolyte represented by the following chemical formula 1: (Chemical formula 1) Li + 12-n-x A n+ X 2- 6-x Y' - x In the formula 1, A is P, As, Ge, Ga, Sb, Si, Sn, Al, In, Ti, V, Nb or Ta; X is S, Se or Te, and Y' is Cl, Br, I, F, CN, OCN, SCN or N 3 where 1≦n≦5 and 0≦x0≦2.
15. The argyrodite-type solid electrolyte is Li 7-x P.S. 6-x C x (0≦x≦2), Li 7-x P.S. 6-x B x (0≦x≦2) and Li 7-x P.S. 6-x I x The all-solid-state secondary battery according to claim 14 , wherein x is one or more selected from (0≦x≦2).
16. 16. The all-solid-state secondary battery according to claim 1, wherein the first negative electrode active material layer contains a negative electrode active material and a binder, the negative electrode active material has a particulate form, and the negative electrode active material has an average particle size of 4 μm or less.
17. 17. The all-solid-state secondary battery of claim 16, wherein the negative electrode active material comprises at least one selected from a carbon-based negative electrode active material, a metal negative electrode active material, and a semi-metallic negative electrode active material, and the carbon-based negative electrode active material comprises at least one selected from an amorphous carbon and a crystalline carbon.
18. The all-solid-state secondary battery according to claim 17, wherein the metal negative electrode active material or the semi-metal negative electrode active material includes one or more selected from the group consisting of gold (Au), platinum (Pt), palladium (Pd), silicon (Si), silver (Ag), aluminum (Al), bismuth (Bi), tin (Sn) and zinc (Zn).
19. 19. The all-solid-state secondary battery according to claim 1, further comprising a second negative electrode active material layer disposed between the negative electrode current collector and the first negative electrode active material layer, the second negative electrode active material layer being a metal layer or a deposit layer containing lithium or a lithium alloy.
Citation Information
Patent Citations
Electrolyte and secondary battery
JP2010225511A
All-solid battery manufacturing method
JP2017130281A
All-solid battery
JP2019087348A
All-solid type secondary battery
JP2019145299A
Electrode for secondary batteries, secondary battery, method for producing electrode for secondary batteries, and method for producing secondary battery
WO2018088193A1